Recht und Gerechtigkeit im Lukasevangelium - Sommer, Michael 1984- (2023)
This article focuses on the relationship between law and justice in Luke’s Gospel. In particular, it examines the narrative development of a concept of justice which Luke lays down in the first chapter of his book and which recurs as a Leitmotif throughout his narrative. This narrative line reaches a climax in the crucifixion scene, in which Luke stylises his Jesus figure as the archetypical exemplar of justice.